Predicting Protein Disorder and Induced Folding: From Theoretical Principles to Practical Applications - Bourhis, Jean M.; Canard, Bruno; Longhi, Sonia (Current Protein and Peptide Science, 2007)
In the last years there has been an increasing amount of experimental evidence pointing out that a large number of proteins are either fully or partially disordered (unstructured). Intrinsically disordered proteins are ubiquitary proteins that fulfil essential biological functions while lacking highly populated and uniform secondary and tertiary structure under physiological conditions. Despite the large abundance of disorder, disordered regions are still poorly detected. Recognition of disordered regions in a protein is instrumental for reducing spurious sequence similarity between disordered regions and ordered ones, and for delineating boundaries of protein domains amenable to crystallization. As presently none of the available automated methods for prediction of protein disorder can be taken as fully reliable on its own, we present a brief overview of the methods currently employed highlighting their philosophy. We show a few practical examples of how they can be combined to avoid pitfalls and to achieve more reliable predictions. We also describe the currently available methods for the identification of regions involved in induced folding and provide a few practical examples in which the accuracy of predictions was experimentally confirmed.
Keywords: prediction methods